A bibliometric study of the research output at the department of economics, the National University of Singapore. - Ng, Hsin Min. (2008)
The study of economics has been in existence since pre-historic times. In this dissertation, bibliometrics techniques are applied to examine the nature of the research output of the Department of Economics in the National University of Singapore. The study covers a ten-year period from 1994 to 2003 and extracts the number of publications - sspecifically journal articles and book reviews - for analysis. The number of publications produced by the Department has fluctuated over the ten-year period on an annual basis, with no obvious trend in sight. On an aggregated basis, the Department's academic staff produced a total of 399 journal articles, 31 book reviews, 163 book chapters, 48 books, 437 monographs/conference papers and 48 newspaper articles.